Blends of shellac as nanofiber formulations for wound healing - Vannuruswamy, Garikapati; Rathna, Gundloori Venkata Naga; Gadgil, Bhagyashri Shashikant Thorat; Gadad, Anand Panchakshari (Journal of Bioactive and Compatible Polymers, 2015)
Shellac is being used in food, pharmaceutical, and agricultural industries. It is seldom used for biomedical applications due to its poor mechanical property and instability. We designed thermoresponsive shellac-based bioactive nanofiber mats that mimic extracellular matrix to extend their utility in wound healing. Various blend compositions of shellac, gelatin, and poly(N-isopropylacrylamide) enriched with a bioactive agent, nadifloxacin, were prepared and nanofiber mats were fabricated. The morphology of the nanofiber formation was influenced by the concentration of polymer, drug, and polymer blend composition. Polymer-drug interactions and thermal and crystalline properties of nanofiber mats were analyzed. The shellac/gelatin/poly(N-isopropylacrylamide) blend of composition 3%/7%/3% (w/v) was chosen to evaluate in vitro drug release. Release studies recorded slow, constant, and sustained release for 140h. The release kinetics and mechanism confirmed zero-order release with resultant r(2) values greater than 0.99, and the Korsmeyer-Peppas release exponent (n) was slightly higher than 0.8, which indicated that drug diffusion was anomalous or non-Fickian type and drug release followed diffusion involving chain stretching. Indirect cytotoxicity studies recorded insignificant toxicity against normal human fibroblast cells. In vivo studies demonstrated that drug-loaded nanofiber mats were more suitable for faster tissue regeneration as compared to nanofiber mats without drug and commercial nadifloxacin cream.
Keywords: drug release and mechanism; nanofibers; Shellac; thermoresponsive; tissue regeneration